2021
DOI: 10.1136/bcr-2020-237669
|View full text |Cite
|
Sign up to set email alerts
|

Rectovaginal extragastrointestinal stromal tumour (EGIST): an additional entity to be considered in the differential diagnosis of tumours of the rectovaginal septum

Abstract: Gastrointestinal stromal tumours (GISTs) are rare - and rectovaginal extragastrointestinal stromal tumours (RV-EGISTs) even rarer. We share a case of RV-EGIST, complemented by high-quality radiological and surgical images. A review of current literature pertaining to RV-EGIST is also included. Our case report highlights the diagnostic challenge presented by extragastrointestinal stromal tumours. Differentiated from overlapping pathologies only by targeted application of immunohistopathology and cytogenetics, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer [17][18][19][20][21][22][23][24][25]. Achieving resection of all macroscopic disease (R0) is the single independent factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer [17][18][19][20][21][22][23][24][25]. Achieving resection of all macroscopic disease (R0) is the single independent factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Achieving resection of all macroscopic disease (R0) is the single independent factor for survival. In their meta‐analysis including 6885 patients with advanced ovarian cancer, Bristow et al (2023) have shown there is a 5.5% increase in median survival time with each 10% increase in maximal cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer 18–26 . Achieving resection of all macroscopic disease (R0) is the single independent factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, it has been shown that surgical MDTs can decrease peri‐ 18 and postoperative 19 mortality. Due to the complexity of pelvic anatomy and the broad array of structures contained within it, MDT surgical collaboration has often been described for pelvic and other gynecological surgeries, resulting in successful patient outcomes 20–22 . Overall, this approach was effectively utilized to maximize the chance of eradication of disease from the perineum, minimizing recurrence risk which should have a significant and positive impact on the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of pelvic anatomy and the broad array of structures contained within it, MDT surgical collaboration has often been described for pelvic and other gynecological surgeries, resulting in successful patient outcomes. [20][21][22] Overall, this approach was effectively utilized to maximize the chance of eradication of disease from the perineum, minimizing recurrence risk which should have a significant and positive impact on the patient's quality of life. Ongoing MDT input will be essential to continue to manage her hidradenitis suppurativa, with medical specialty involvement, such as dermatology, hopefully meaning that further surgical intervention is not necessitated.…”
Section: Outcome and Follow-upmentioning
confidence: 99%